Keseimbangan Peran Keluarga pada Remaja Generasi Sandwich dalam Mewujudkan Kesehatan Mental yang Optimal - Nurdiansyah, Putra Pandu Dinata; Ch, Mufidah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study discusses the balance of family roles in Sandwich Generation adolescents in realizing optimal mental health. The background of this study is the increasing pressure faced by adolescents who have to take care of parents and children simultaneously, which often has a negative impact on their mental health. The purpose of this study is to examine how Sandwich Generation adolescents balance their roles in the family and its impact on their mental health. The method used was desk research with a phenomenological qualitative approach to understand adolescents' subjective experiences. The results showed that balanced family support can reduce stress and improve mental health, while role imbalance can lead to emotional problems, such as anxiety and depression. The conclusion of this study emphasizes the importance of the family's role in creating a supportive environment for Sandwich Generation adolescents to effectively manage their responsibilities and maintain optimal mental health.